Potential Blood Biomarker for Disease Severity in the Taiwanese Population With Alzheimer's Disease. (February 2013) - Huang, Ching-Wen; Wang, Shang-Jang; Wu, Shyh-Jong; Yang, Ching-Chung; Huang, Ming-Wei; Lin, Chieh-Hsin; Cheng, Irene H.
The identification of blood biomarkers for Alzheimer's disease (AD) could contribute for improvement in early diagnosis. To define AD biomarkers, we compared serum/plasma levels of amyloid β (Aβ), tau, cytokines, and biometals between AD and non-AD groups. Cognitive impairment was assessed by Mini-Mental Status Examination (MMSE) and Clinical Dementia Rating scales. Plasma concentrations of total Aβ, Aβ42, tumor necrosis factor α (TNF-α), and interleukin 6 were quantified by immunoassays. Serum biometal concentrations were determined using flame atomic absorption spectrometry. We found that serum zinc (Zn) was lower in patients with AD. After controlling for age, the MMSE score correlated with both TNF-α and total Aβ levels in the AD group, while the MMSE score correlated with iron only in the non-AD group. Our finding that blood Zn, TNF-α, and total Aβ are possible biomarkers for AD diagnosis and prognosis validates the pervious publication on potential biomarker in the Taiwanese population.